READING COMPREHENSION PROBLEMS OF TOEIC FACED BY ACCOUNTING MANAGERIAL STUDENTS - Sektalonir Oscarini Wati Bhakti (Politeknik Negeri Bengkalis, 2022)
100 students of eight-semester students of Accounting Managerial Program Politeknik Negeri Samarinda were the participants of this research. The aim of this research was to find out the reading comprehension problems in reading section of TOEIC Prediction test. TOEIC Prediction Test is one of English Proficiency Tests that has to be participated by 800 last semester students. Adapted questionnaire from Wutthisingchai (2011) was used as an instrument in this research since this research was a descriptive qualitative. The questioner was consisted of five aspects; reading comprehension process, motivation, background knowledge, lack reading strategies, and language knowledge. Thus, to measure the students’ perception of reading, the 4-point Likert was used in this research.The results of the research showed that most of the students of eight-semester students of Managerial Accounting Program still had reading comprehension problems.Keywords: Reading Comprehension Problems, descriptive qualitative, TOEIC